A retrospective review of endogenous endophthalmitis: three years of experience at Sultan Ahmad Shah Medical Centre at International Islamic University Malaysia - Alias, Nur Syifa Athirah Qistina; Abu Bakar, Mohd Fadzil; Rosli, Abdul Hadi; Jabbari, Aidila Jesmin (Springernature, 2024)
Introduction Endogenous endophthalmitis is characterized by severe intraocular inflammation caused by the invasion of microorganisms into the anterior and posterior chambers of the eye. It results from hematogenous spread from distant foci of infection. This, in turn, leads to potential vision loss and blindness due to reduced anatomical and functional outcomes. The latest reported prevalence of endogenous endophthalmitis accounts for at least 2-8% of cases of general endophthalmitis which is fairly significant.